The performance assessment of government bonds among COVID-19 affected top-10 countries - Muhammad Nadiy, mat Noh (2021)
The unprecedented worldwide epidemic of COVID-19 has had a significant impact on the government bond market, both in terms of yield responses and volatility impacts. This study investigates the short run and long run performance of 3-month, 1-year, 5-year and 10-year government bond of the top-10 COVID-19 affected countries which are United States, India, Brazil, Russia, United Kingdom, France, Spain, Italy, Turkey and Germany during the year 2020. Using collected data from S&P Global and Investing.com, an event study technique and GARCH Model are developed to analyze the reactions of government bond yield during the period of the pandemic. The findings of the Event Study suggested that COVID-19 had significant effect on the government bond yield in some of the countries studied. The Event Study Analysis showed that most studied countries recoded negatively significant result before and after the announcement of first confirmed case of COVID-19 hit these countries. The findings in GARCH Model also suggested that COVID-19 had significant effect on the bond yield’s velocity. These findings proved that COVID-19 had a significant impact on these countries' government bond yield performance. The findings are expected to help policymakers, governments, investors and traders to predict the immediate outcomes of their investments or decisions making. The limitation is that this study only focusses on 3-month, 1-year, 5-year and 10-year government bond of the top-10 COVID-19 affected countries. Future study might concentrate on other countries or different government bond maturities.